Orthopaedic Foot and Ankle Surgeon Industry Compensation Reported by the Open Payments Database. Issue 2 (April 2021) - Pathak, Neil; Galivanche, Anoop R.; Lukasiewicz, Adam M.; Mets, Elbert J.; Mercier, Michael R.; Bovonratwet, Patawut; Walls, Raymond J.; Grauer, Jonathan N.
Background . The current study aims to characterize and explore trends in Open Payments Database (OPD) payments reported to orthopaedic foot and ankle (F&A) surgeons. OPD payments are classified as General, Ownership, or Research. Methods . General, Ownership, and Research payments to orthopaedic F&A surgeons were characterized by total payment sum and number of transactions. The total payment was compared by category. Payments per surgeon were also assessed. Median payments for all orthopaedic F&A surgeons and the top 5% compensated were calculated and compared across the years. Medians were compared through Mann-Whitney U tests. Results . Over the period, industry paid over $39 million through 29, 442 transactions to 802 orthopaedic F&A surgeons. The majority of this payment was General (64%), followed by Ownership (34%) and Research (2%). The median annual payments per orthopaedic F&A surgeon were compared to the 2014 median ($616): 2015 ($505; P = .191), 2016 ($868; P = .088), and 2017 ($336; P = .084). Over these years, the annual number of compensated orthopaedic F&A surgeons increased from 490 to 556. Averaged over 4 years, 91% of the total orthopaedic F&A payment was made to the top 5% of orthopaedic F&A surgeons. The median payment for this group increased from $177 000 (2014) to $192 000 (2017; P = .012). Conclusion . Though median payments to the top 5% of orthopaedic F&A surgeons increased, there was no overall change in median payment over four years for all compensated orthopaedic F&A surgeons. These findings shed insight into the orthopaedic F&A surgeon-industry relationship. Levels of Evidence: III, Retrospective Study